Musmos [videorecording] ([Quezon City] The Center, 1992)
A video situationer on child beggars, victims of war and armed conflicts and street children.
Christin Joy Alfuente, child narrator.
Keywords: Child abuse -- Philippines; Children -- Employment -- Philippines; Poor children -- Philippines; Sociology